2016
DOI: 10.1002/fut.21785
|View full text |Cite
|
Sign up to set email alerts
|

Price Discovery and Foreign Participation in Korea's Government Bond Futures and Cash Markets

Abstract: This paper examines the impact of foreign participation in Korean Treasury Bond (KTB) futures and its role in price discovery, using daily transactions data from the over‐the‐counter market and from the Korea Exchange for the futures. Our analysis suggests that foreign trading in the KTB futures market leads the price discovery process for the underlying bonds. Empirical results show that foreigners’ daily net long positions in the futures market exert significant influence in KTB and KTB futures prices. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Further, Orlowski (2015) found that electronic trading mechanism significantly reduced the price volatility of US Treasury futures. Park et al (2017) analyzed the impact of foreign investors' participation on the price volatility of Korean Treasury futures. Therefore, the price volatility of Treasury futures is affected by the economic policy and trading mechanism among other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Orlowski (2015) found that electronic trading mechanism significantly reduced the price volatility of US Treasury futures. Park et al (2017) analyzed the impact of foreign investors' participation on the price volatility of Korean Treasury futures. Therefore, the price volatility of Treasury futures is affected by the economic policy and trading mechanism among other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examine price discovery in commodity futures markets with mixed findings. Garbade and Silber (1983) report that wheat, corn, and orange juice futures lead spot markets. Hauptfleish et al (2016) reach a similar conclusion in gold futures markets.…”
mentioning
confidence: 99%